The Addition of Potato Biscuit in the Feed of Sumatran Slow Loris (Nycticebus coucang Boddaert, 1785) and Javan Slow Loris (Nycticebus javanicus Geoffroy, 1812): The effects on Digestibility and Feed Efficiency - Farida, Wartika Rosa; Sari, Andri Permata; Astuti, Wulansih Dwi (JURNAL BIOLOGI INDONESIA, 2016)
ABSTRACTThis experiment aims to determine the effect of the addition of potato biscuit on digestibility and feed efficiency in Sumatran slow loris (Nycticebus coucang). Research has been conducted on Small Mammals Captivity Breeding of Zoology Division, Research Center for Biology - LIPI for 66 days consisting of a 10 days adaptation period of feed and 56 days (8 weeks) data collection period. The material used is four Sumatran slow lorises (N. coucang) and two Javan slow lorises (N. javanicus). Feed given during the study are banana, papaya, dragon fruit, guava, passion fruit, boiled sweet potato, boiled egg potato biscuits, crickets, and meal worm. Feed treatment to Sumatran slow loris consisting of feed control (T0) and T0 plus potato biscuits (T1), while Javan slow loris was only fed T1 as a comparison. Parameters measured were consumption, digestibility, and feed efficiency. The most palatable feed types for Sumatran slow loris and Javan slow loris are banana, cricket, and meal worm. Mean of feed intake at T0 and T1 treatment was 38.63 and 37.42 g / head / day, and that of Javan slow loris is 42.51 g / head / day. Mean of dry matter digestibility of Javan slow loris> T1> T0, namely 92.02%, 91.21%, and 88.95% respectively; whereas the highest average feed efficiency (EPP) is at 12.06% for Sumatran Slow loris and 9.10% in Javan slow loris. The average of total digestible nutrients (TDN) of Javan slow loris> T1> T0, namely 87.04%, 85.34%, and 83.54% respectively.Keywords: consumption, digestibility, feed utilization, Nycticebus coucang, Nycticebus javanicus